Aspek-aspek perkembangan psikologi anak didik sesuai perspektif studi Islam - Rohman, Inayatur; Maulana Putra, Muhammad Rifky; Triwisuda Ningsih, Endah (Jurnal Pendidikan Agama Islam, 2025)
Problems in individual development include motor delays, intellectual disabilities, learning and communication difficulties, as well as the inability to manage emotions properly. These problems indicate that each individual has differences in the speed and quality of development, which are influenced by internal factors such as genetics and health conditions, as well as external factors such as family environment, education, and social surroundings. The main goal of development is to help individuals achieve balance in physical, intellectual, emotional, and language aspects so that they are able to think logically, interact socially in a healthy manner, and communicate effectively. To achieve this goal, various methods can be applied, including cognitive stimulation to enhance thinking ability and creativity, behavioral and social interaction observation to understand and train emotional abilities, motor exercises to improve body strength and coordination, and language development through active communication in daily environments. The outcomes of physical, intellectual, emotional, and language development are important aspects of a child’s growth that are interconnected and influence one another. Therefore, all of these aspects need to be monitored and supported through scientific approaches such as observation, experimentation, and targeted stimulation so that children can reach their optimal potential according to their developmental stage. With proper attention and support, the process of individual development can occur in a balanced manner and result in individuals who are intelligent, healthy, and able to adapt to their environment.